2012
DOI: 10.1002/ana.23642
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: 5‐Lipoxygenase gene transfer worsens memory, amyloid, and tau brain pathologies in a mouse model of alzheimer disease

Abstract: Objective The 5-lipoxygenase (5LO) enzyme is up-regulated in Alzheimer’s disease (AD), and its genetic absence reduces Aβ levels in APP mice. However, its functional role in modulating tau neuropathology remains to be elucidated. Methods To this end, we generated triple transgenic mice (3xTg-AD) over-expressing neuronal 5LO and investigated their phenotype. Results Compared with controls, 3xTg-AD mice over-expressing 5LO manifested an exacerbation of memory deficits, plaques and tangles pathologies. The el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 74 publications
(106 citation statements)
references
References 30 publications
(88 reference statements)
2
104
0
Order By: Relevance
“…This concentration and incubation time were chosen based on previous studies conducted by our group. Specifically, we found that this concentration and incubation time produced the most efficient effect of suppressing cdk5 activity (Chu et al ., 2012b). As seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This concentration and incubation time were chosen based on previous studies conducted by our group. Specifically, we found that this concentration and incubation time produced the most efficient effect of suppressing cdk5 activity (Chu et al ., 2012b). As seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The cells were cultured to 70% confluence in six‐well plates and then transfected with 1 μg empty vector or human 5LO pcDNA3.1 (Dr. Colin Funk, Queen's University, Kingston, Canada) using Lipofectamine reagent (Invitrogen) according to the manufacturer's instructions and as previously described (Chu et al ., 2012b). After 48‐h treatment, supernatants were collected and cell harvested in lytic buffer for biochemistry analyses.…”
Section: Methodsmentioning
confidence: 99%
“…We utilized We corroborated these findings of Aβ pathology in the 3xTg mouse and found that additionally, 5LO also acts on tau metabolism. Genetic unavailability of 5LO or its overexpression correlates directly with increased and diminished, respectively, tau phosphorylation, insoluble tau aggregation and NFT development [35,36]. We have shown that this aspect of 5LO is mediated by the cyclin-dependent kinase 5 (cdk5) [37].…”
Section: -Lipoxygenase: a Modulator The Alzheimer's Disease Phenotypementioning
confidence: 98%
“…In vivo overexpression of 5-LOX increases phosphorylation of specific Tau epitopes, and neuronal cells transfected with 5-LOX show a significant increase in tau phosphorylation even when their ability to generate Aβ is completely blocked, suggesting that the effect on tau is independent from Aβ (Chu et al, 2012). Interestingly, Tau-mice treated with zileuton (a potent 5-LOX inhibitor) displayed a significant improvement in memory and synaptic function together with a decreased tau phosphorylation level (Chu and Pratico, 2013;Giannopoulos et al, 2014).…”
Section: How Do N-3 Pufa Mechanisms Control Neuroinflammation?mentioning
confidence: 99%